Wealth-based inequality in underweight among Scheduled Tribe women in India: a regional analysis - Anshika Singh; Aditya Singh; Mahashweta Chakrabarty; Shivani Singh; Pooja Tripathi (International Journal for Equity in Health)
Abstract Background Despite widespread undernutrition among tribal women, there is limited understanding of wealth-based disparities in underweight within this group and how these inequities have changed over time across different regions of India. This study aims to explore trends and patterns of wealth-based inequalities in underweight prevalence among Scheduled Tribe (ST) women across various regions of India. Methods The study analysed data from the fourth and fifth rounds of the National Family Health Survey, covering 113,549 and 121,326 non-pregnant ST women aged 15–49, respectively. Wealth-based inequality in underweight was assessed using the Erreygers normalized concentration index (ECI), while predicted probabilities of underweight, adjusted for relevant variables, were calculated using binary logistic regression. Findings Between 2015-16 and 2019-21, underweight prevalence among ST women in India decreased from 31.7 to 25.5%, with all regions showing declines. The northern region witnessed the largest drop (20.1–9.8%), followed by the western region (38.7–30.0%) and eastern-central region. The northeastern region that had consistently low underweight prevalence witnessed minimal change over the study period. Wealth inequality, as measured by the ECI, slightly decreased over the study period, from − 0.177 in 2015–16 to -0.134 in 2019–21. However, the reduction in ECI varied significantly across regions. The northern region experienced the most significant reduction in wealth inequality, with a decrease of -0.145 ECI points. In comparison, the western, southern, eastern-central regions exhibited more modest reductions of -0.036, -0.027, and − 0.028 ECI points, respectively. The northeastern region, characterized by initially lower levels of inequality, demonstrated no change in its ECI over the study period. The predicted probabilities from the pooled logistic regression analysis indicated a decline in inequality over the study period. This reduction was primarily driven by significant decreases in underweight prevalence among the poorer and poorest wealth quintiles. Notably, the northern, western, eastern-central, and southern regions experienced the most pronounced improvements in underweight prevalence among these lower wealth groups. Despite overall progress, wealth-based inequality in underweight persisted, especially in the western, southern, and eastern-central regions, where the 2019-21 ECI remained more than − 0.10. Conclusion Despite progress in reducing underweight among ST women in India, regional disparities and wealth-based inequality in underweight persist. Policies should focus on targeted, region-specific interventions that prioritize economically disadvantaged women, reduce inequality, and improve access to nutrition and healthcare, particularly in the western, southern, and eastern-central regions.